Isospin-breaking contribution to the model-independent axion-photon-photon coupling in U(3) chiral theory - Rui Gao; Jin Hao; Chun-Gui Duan; Zhi-Hui Guo; J. A. Oller; Hai-Qing Zhou (European Physical Journal C: Particles and Fields)
Abstract We pursue the calculation of the model-independent component of the axion-photon-photon coupling in the U(3) chiral perturbation theory up to next-to-leading order, with the emphasis on the isospin breaking effect. The mixing of the $$π ^0$$ π 0 - $$η $$ η - $$η '$$ η ′ -axion system is revised as well by working out the complete linear isospin-breaking terms. Our calculation shows that the isospin-breaking correction to the axion-photon-photon coupling amounts to more than 15%, comparing with the result in the isospin limit.